Hubungan Kejelasan Bicara dengan Kemampuan Bahasa Pragmatik pada ABK Sekolah Dasar Inklusi di Surakarta - Fitri, Anisyah Dewi Syah; Setyaningsih, Wiwik (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Abstract Background: This research was motivated by the problem of children with special needs having difficulty in developing interactive conversations. This happens because they have difficulty understanding and predicting other people's thoughts and feelings. They consider the process of changing listening and explaining to be very difficult to do. They don't know what to focus on and how to respond back to their conversation partners, which results in crew members becoming less confident every time they speak. The required components of speech clarity and pragmatic language include non-verbal communication, conversation initiation and maintenance, while structural language, is a narrower category of skills that includes syntax, articulation and phonology. Objectives: This research aims to determine the relationship between speech clarity and pragmatic language skills in inclusive elementary school students in Surakarta. Methods: This type of research is quantitative with a correlational descriptive design. The data collection technique uses purposive sampling technique. Data was taken using the Assessing Intelligibility Worksheet questionnaire and the pragmatic language ability questionnaire. Next, the data was analyzed using the chi-square correlation test. Results: Univariate respondents with male gender were 22 children (73.3%) and 8 children female (26.7%). The speech clarity results of 10 children (33.3%) were average and 20 children (66.7%) were below average. The results of pragmatic language ability showed that 7 children (23.3%) were capable. 23 children (76.7%) are not yet capable. The results of the bivariate analysis obtained the value of ρ is 0.836 where the value of ρ≥0.05, which can be interpreted as Ha being rejected and Ho being accepted. Conclusion: There is no relationship between speech clarity and pragmatic language skills in inclusive elementary school students in Surakarta. Keywords : Speech clarity, Pragmatics, ABK, Inclusion, Elementary School